2018
DOI: 10.1177/1176934318790265
|View full text |Cite
|
Sign up to set email alerts
|

bHLH13 Regulates Jasmonate-Mediated Defense Responses and Growth

Abstract: Jasmonates (JAs) regulate plant growth and defense responses. On perception of bioactive JAs, the JA receptor CORONATINE INSENSITIVE1 (COI1) recruits JA ZIM-domain (JAZ) proteins for degradation, and JAZ-targeted transcription factors are released to regulate JA responses. The subgroup IIId bHLH transcriptional factors, including bHLH17, bHLH13, bHLH3, and bHLH14, interact with JAZs and repress JA responses. In this study, we show that IIId bHLH factors form dimers via the C-terminus in yeast. N-terminus of bH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This significant decrease in anthocyanin production could be explained by the previously described function of the bHLH13 (JAM2) and bHLH17 (JAM1) transcription factors that act as the transcriptional repressors which negatively regulate JA responses resulting in anthocyanin reduction in transgenic plants [ 50 , 51 , 61 , 62 , 63 ]. Furthermore, it has also been reported that bHLH17 is a bHLH subgroup III transcription factor which acts as a transcriptional repressor after binding to the promoters of the target genes in the anthocyanin-regulating pathway [ 64 ], which antagonizes the activation function of MYC2 and TT8/MYB75 to negatively regulate JA responses including flowering and anthocyanin accumulation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This significant decrease in anthocyanin production could be explained by the previously described function of the bHLH13 (JAM2) and bHLH17 (JAM1) transcription factors that act as the transcriptional repressors which negatively regulate JA responses resulting in anthocyanin reduction in transgenic plants [ 50 , 51 , 61 , 62 , 63 ]. Furthermore, it has also been reported that bHLH17 is a bHLH subgroup III transcription factor which acts as a transcriptional repressor after binding to the promoters of the target genes in the anthocyanin-regulating pathway [ 64 ], which antagonizes the activation function of MYC2 and TT8/MYB75 to negatively regulate JA responses including flowering and anthocyanin accumulation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OPR3 gene was chosen for encoding one of the key enzymes involved in JA-synthesis [ 62 ], as well as the genes MYC2 and EIN3 for being regulators of JA and ET responsive genes [ 63 , 64 ], respectively. Additionally, we selected the THI2-like gene that encodes a JA-induced thionin with antimicrobial properties [ 65 ] and the bHLH13 gene for being a MYC2 repressor [ 66 ]. Finally, we chose the transmembrane PIP2 gene involved in the microbial recognition and elicitation of the immune response [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…CmbHLH59 is an MYC-type protein that is differentially expressed from developmental to ripening stages in melon fruit. The CmbHLH59 sequence is similar to ATbHLH13 in Arabidopsis, and the functions of ATbHLH13 are repressing Arabidopsis defense responses and regulating anthocyanin biosynthesis through JA signaling pathway [44,45]. CmbHLH114 was upregulated in R vs. C stage samples, and CmbHLH114 was annotated to an ICE1-like gene.…”
Section: Potential Roles Of Cmbhlh Genes In Melon Fruit Developmenmentioning
confidence: 99%